HUBUNGAN FAMILY SUPPORT DENGAN KEPATUHAN MENGONSUMSI ARV PADA ODHA - Irfandi Rahman; Wahyuni Maria Prasetyo Hutomo; Baktianita Ratna Etnis (Nursing Arts, 2023)
PLWHA but in reality it appears that there are still around 20.2% of PLWHA who are actively taking ARV therapy while the rest of PLWHA are no longer actively taking ARV therapy. Based on the data obtained, the researcher aims to determine the relationship between family support and adherence to taking ARV in PLWHA at the Malanu Public Health Center, Sorong City. This research method uses the type of quantitative research with cross sectional approach. The population of this study was PLWHA who were recorded at the Malanu Public Health Center, amounting to 208 people, while the research sample found 36 respondents. The sampling technique used is accidental sampling. The research instrument used is a questionnaire and the statistical test used is the chi square test. The results of this study indicate that there is a correlation between family support and adherence to taking ARV in PLWHA at the Malanu Health Center in Sorong City using a p-value of 0.000 <0.05. the conclusion is that there is a relationship between family support and adherence to taking ARV in PLWHA at the Malanu Health Center. Suggestions for Puskesmas to be able to include active families in KDS so that PLWHA are interested in taking therapy and comply with ARV treatment.